Assessing mental health during pregnancy: An exploratory qualitative study of midwives' perceptions. (July 2020) - Baker, Natasha; Gillman, Lindsay; Coxon, Kirstie
Abstract: Background: Mental health disorders are estimated to affect between 10% and 20% of women who access maternity services and can be defined as a public health issue due to the potential consequences for women, children and families. Detecting problems early in pregnancy can significantly improve outcomes for women and their families. However, mental health problems are not being consistently identified in routine midwifery practice and little is known from current literature about midwives' practice in relation to current national guidelines or the impact models of care have on assessing maternal mental health. Objective: To identify midwives' views about barriers and facilitators to screening for mental health in pregnancy using current UK guidelines. Design: Nine community midwives from a single district general hospital in the south of England were recruited to take part in focus groups. Thematic analysis was used to extract key themes from the data. Findings: Three key themes were identified from the focus groups and included system factors, social factors and trust. Barriers and facilitators to screening maternal mental health were associated with the initial 'booking' appointment' and differences in models of care. Barriers to screening were defined as high workload, poor continuity, and a lack of trust between women and midwives. Conclusions: This study highlights key barriers and facilitators associated with mental health screening during pregnancy, including issues of trust and uncertainty about women's willingness to disclose mental health conditions. Further research is required to evaluate the relationship between women and midwives in contemporary practice and the influence this may have on maternal mental health.